Characterization of Wnt/β-catenin and BMP/Smad signaling pathways in an in vitro model of amyotrophic lateral sclerosis - Pinto, Cristina; Cardenas, Pilar; Osses, Nelson; Henríquez, Juan Pablo (Frontiers in Cellular Neuroscience, 2013)
Different pathways activated by morphogens of the early embryonic development, such as the Wnt and the Bone Morphogenetic Protein (BMP) ligands, are involved in diverse physiological and pathological conditions of the nervous system, including neurodegeneration. In this work, we have analyzed the endogenous activity of the canonical Wnt/β-catenin and BMP/Smad-dependent pathways in an in vitro model of amyotrophic lateral sclerosis (ALS), given by motor neuron-like NSC34 cells stably expressing wild-type or G93A mutated forms of human Cu/Zn superoxide dismutase-1 (SOD1). As ALS-derived motor neurons, NSC34 cells expressing mutated hSOD1 show a decreased proliferation rate, are more susceptible to oxidation-induced cell death and display Golgi fragmentation. In addition, they display an impaired ability to induce the expression of the motor neuronal marker Hb9 and, consistently, to morphologically differentiate into a motor neuronal phenotype. Regarding signaling, our data show that the transcriptional activity associated to the Wnt/β-catenin pathway is decreased, a finding possibly associated to the cytosolic aggregation of β-catenin. In turn, the BMP-dependent phosphorylation of Smad1 and the transcriptional activation of the BMP/Smad pathway is increased in the pathologic model. Together, these findings suggest that Wnt/β-catenin and the BMP-dependent pathways could play relevant roles in the neurodegeneration of motor neurons in the context of ALS.